2017
DOI: 10.17743/jaes.2017.0028
|View full text |Cite
|
Sign up to set email alerts
|

Sound Source and Loudspeaker Base Angle Dependency of Phantom Image Elevation Effect

Hyunkook Lee

Abstract: Early studies found that, when identical signals were presented from two loudspeakers equidistant from the listener, the resulting phantom image was elevated in the median plane and the degree of the elevation increased with the loudspeaker base angle. However, sound sources used in such studies were either unknown or limited to noise signals. In order to investigate the dependencies of the elevation effect on sound source and loudspeaker base angle in details, the present study conducted listening tests using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The 4 kHz band is mapped to 'front' localisation by Blauert. However, in a phantom image condition, which is the case in the present study, Lee [23] showed that, with a pair of loudspeakers elevated at 30° from the listener's ear position, a 4 kHz octave band noise was perceived to be elevated at the same height as the loudspeakers, due to the phantom image elevation effect [24,25]. Therefore, by reducing the energy of this band in the height layer, the perceived elevation of a phantom image that results from the vertical quadraphonic reproduction might be reduced.…”
Section: Test Stimulimentioning
confidence: 89%
“…The 4 kHz band is mapped to 'front' localisation by Blauert. However, in a phantom image condition, which is the case in the present study, Lee [23] showed that, with a pair of loudspeakers elevated at 30° from the listener's ear position, a 4 kHz octave band noise was perceived to be elevated at the same height as the loudspeakers, due to the phantom image elevation effect [24,25]. Therefore, by reducing the energy of this band in the height layer, the perceived elevation of a phantom image that results from the vertical quadraphonic reproduction might be reduced.…”
Section: Test Stimulimentioning
confidence: 89%
“…Informal auditioning of the synthesized stimuli, using the above BRIRs, revealed that the excerpts representing the BF scene had distinctively different timbral characteristics (being perceived as "duller") and appeared to be elevated, compared to those exhibiting the FB scene. The elevation effect could be explained by the fact of using binaural responses from the widely spaced loudspeakers (±110 • ), as demonstrated by Lee [39].…”
Section: Database Of Binaural Room Impulse Responsesmentioning
confidence: 96%
“…These directional bands yielded spatial perception in the median plane that were independent of the actual location of the sound source [13]. The frequency dominance in vertical localization reported in those studies also implies the illusory elevation of a sound source, which has been investigated in various studies until present [27][28][29][30][31][32][33][34][10][11][12].…”
Section: Spatial Hearing Research On Vertical Localizationmentioning
confidence: 99%
“…Lee extensively investigated the illusory sound source elevation effect from a pair of symmetrically positioned loudspeakers [32][33][34][10][11][12]. This phenomenon, referred to as the phantom image elevation effect, appears when two loudspeakers in the horizontal plane emit the same signal, thus creating a "phantom image" at the midpoint of the loudspeaker pair.…”
Section: Spatial Hearing Research On Vertical Localizationmentioning
confidence: 99%